Efficacy of combined CD38 and PD-1 inhibition with isatuximab and cemiplimab for relapsed/refractory NK/T-cell lymphoma - Kim, Seok Jin; Lim, Jing Quan; Yoon, Sang Eun; Yang, Deok-Hwan; Lee, Ji Hyun; Oh, Sung Yong; Choi, Yoon Seok; Jeong, Seong Hyun; Kim, Min Kyoung; Lim, Sung Nam; Cho, Junhun; Park, Bon; et al. (American Society of Hematology, 2025)
This study aimed to assess the efficacy and safety of combining cemiplimab, an anti–programmed cell death protein 1 (PD-1) antibody, with isatuximab, an anti-CD38 antibody, in relapsed or refractory extranodal natural killer/T-cell lymphoma (R/R ENKTL). The hypothesis was that CD38 blockade could enhance the antitumor activity of PD-1 inhibitors. Eligible patients received cemiplimab (250 mg on days 1 and 15) and isatuximab (10 mg/kg on days 2 and 16) IV every 4 weeks for 6 cycles. Responders then received cemiplimab (350 mg) and isatuximab (10 mg/kg) every 3 weeks for up to 24 months. The primary end point was the complete response (CR) rate based on the best response. Of 37 patients enrolled, the CR rate was 51% (19/37), exceeding the primary end point of 40%, and the objective response rate was 65% (24/37). After a median follow-up of 30.2 months (95% confidence interval [CI], 25.6-34.8 months), the median progression-free survival was 9.5 months (95% CI, 1.4-17.6 months), whereas the median overall survival had not yet been reached. Patients achieving CR received a median of 28 cycles (range, 4-33 cycles), and the median duration of response for responders (n = 24) was 29.4 months (95% CI, 15.4-43.4 months). Structural variations disrupting the 3’-untranslated region of PD-L1 and high programmed death ligand 1 (PD-L1) expression were observed in responders. Most adverse events were mild (grade 1-2), with grade ≥3 events (32%) and no treatment-related deaths. The combination of isatuximab and cemiplimab demonstrated sustained antitumor activity and a manageable safety profile in R/R ENKTL. This phase 2 trial is registered at www.clinicaltrials.gov as number NCT04763616.